DESIGN INTERNATIONAL DISTRIBUTION CHANNEL DIFFERENTIAL AS MARKETING ADVANTAGE: IF TOYOTA - Camargo Hermosilla, Raúl Moisés (2015)
Any product perceived as different from others is a “different product”, although in practice it is similar. Following this approach that places differentiation as a key variable to compete, Physical and functional advantages are needed to participate in a competitive market, but not enough to win the loyalty of users. In the majority of manufacturing, distribution and product support strategic assets are undervalued. Today, excellence in engineering, manufacturing efficiency and quality are quickly becoming elements that are taken for granted.